Validation of AG-Q COVID-19 N-Antigen Self-Test in Comparison with Real Time RT-PCR - Sukumaran, Ajaikumar; Krishnan, Arun; Thomas, Rhema; Paul, Jofy; Vasudevan, D.M (Indian journal of clinical biochemistry, 2022)
Validation of AG-Q COVID-19 N-Antigen Self-Test in comparison with Real Time RT-PCR Ajaikumar Sukumaran, Arun Krishnan, Rhema Thomas, Jofy Paul, D M Vasudevan Introduction Currently, RT-PCR and the rapid antigen test (RAT) are the major stakeholders in COVID-19 diagnosis. The RTPCR is the gold standard testing method and RAT is considered for mass screening of COVID-19. In order to improve the accessibility and pace of diagnosis, ICMR had given permission for COVID-19 self-test by the public. AG-Q COVID-19 N-Antigen Self-Test kit is a home based rapid test kit developed by Agappe Diagnostics Limited. The kit has been validated at NIMS Medicity, Trivandrum and compared the performance with the RT-PCR Ct value. Aim Validation and comparison of AG-Q COVID-19 N-Antigen self-test with RT-PCR. Materials & Methods The AG-Q COVID-19 N-Antigen self-test is a lateral flow immunochromatography based rapid test. The Covipath COVID-19 RT-PCR kit from ThermoFisher Scientific was used for the comparison study. A total of 72 subjects were recruited (30 positive & 42 negative subjects) for the study with the Institutional Ethical Committee approval and informed consent from the subjects. To perform the comparison study, a nasal swab sample in lysis buffe for RAT and a nasopharyngeal swab sample in VTM for RT-PCR were collected from each participants. Result The AG-Q COVID-19 N-Antigen self-test offers 100% specificity with sensitivity of 83.33%. Conclusion As per the study result, the AG-Q COVID-19 N-Antigen self-test is satisfying the ICMR recommended specificity and sensitivity for rapid antigen self-test as compared with the RT-PCR.